Bridging perfectionism and innovation—a moderated-mediation model based on achievement goal theory - Jia, Yingya; Yue, Shuping; Fang, Manci; Wang, Xiaoyu (Frontiers in Psychology, 2025)
IntroductionThere exists a significant gap in the existing literature regarding how and when employee perfectionism impacts innovation performance. This study aims to fill this gap by exploring the relationship between employee perfectionism and innovation performance.MethodsGrounded in achievement goal theory, a moderated-mediation model is proposed. In this model, learning goal orientation acts as a mediator for the distinct influences of negative and positive perfectionism on innovation performance, and perceived failure analysis serves as an organizational culture to moderate this mediation. Survey data from 378 core R&D employees in nine high-tech manufacturing firms in China were collected for analysis.ResultsThe findings reveal that negative perfectionism hinders innovation performance as it fosters avoidance behaviors and risk aversion. On the contrary, positive perfectionism enhances innovation performance by promoting mastery-oriented learning and experimentation. Moreover, perceived failure analysis strengthens the link between positive perfectionism and innovation performance by validating mastery goals and encouraging learning from failures. However, it has no significant effect on the negative perfectionism pathway, since employees with an avoidance orientation perceive failure analysis as a threat rather than a source of useful information.DiscussionThese results contribute to the literature in three aspects. Firstly, they highlight the dual nature of perfectionism in innovation settings. Secondly, they emphasize the mediating role of learning goal orientation in converting perfectionistic tendencies into innovation outcomes. Thirdly, they identify perceived failure analysis as a cultural factor that amplifies the benefits of adaptive perfectionism but fails to mitigate the risks of maladaptive perfectionism. The study also offers practical insights for organizations to utilize the adaptive potential of perfectionism while minimizing its negative impacts.